MINAT PESERTA DIDIK DALAM MENGIKUTI EKSTRAKULIKULER SEPAK BOLA DI SMA MUJAHIDIN PONTIANAK - Wira Irawan; Ahmad Atiq; Fitri Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe mujahidin high school stands firmly on the side of ahmad yani road which is directly oppsite the largest mosque in west Kalimantan province, but from that it is not yet visible to the naked eye whether or not there is sports coaching in mujahidin schools, especially football, so it is important to know the student’s interest in mujahidin school Pontianak the research method used in this study is a quantitative method with a surve reseach from, the population in the his study using purposive sampling. The research results obtained in following the football extracurricular activities.Keywords:Interest of students, football extracurricular